Sumberejo Community's Perspective on Non-Timber Forest Products to Support Sustainable Environment - Sari, Cynthia Permata; Supriyadi; Purwanto; Rosariastuti, Retno; Nufus, Malihatun (Bioeksperimen: Jurnal Penelitian Biologi, 2025)
This study investigates how Non-Timber Forest Resources (NTFPs) contribute to community livelihoods and environmental sustainability. Through a combination of in-depth interviews and participatory observation, this study highlights the traditional knowledge and practices of the Sumberejo community in managing these resources. This research uses a qualitative approach that combines ethnobotanical surveys, in-depth interviews, and participatory observation with 50 participants, as well as data analysis using Participatory Rapid Appraisal (PRA). The results show that the majority of respondents perceive the potential of NFTPs in the area as very important (56.25% of village officials) and important (45.83% of villagers). Respondents also consider the natural geophysical potential for NFTPs in the area to be very important (68.75% of village officials) and important (50% of villagers). Furthermore, respondents also considered the natural biophysical potential for the NFTPs area to be very important (56.25% of village officials) and important (50% of villagers). The study underscores the potential for integrating NTFP management into broader conservation strategies to promote environmental stewardship and sustainable development. The community's commitment to balancing economic needs with environmental health offers valuable insights for policymakers and conservationists aiming to implement community-based forest management models. This research contributes to a growing body of knowledge on the importance of NTFPs in sustainable environmental governance, showcasing the Sumberejo community's role as stewards of their local ecosystems while maintaining cultural heritage and securing economic well being.